A new mite species of Pseudoleptus Bruyant (Tenuipalpidae), and two new records (Tetranychidae, Linotetranidae) reported from the Caspian Sea coasts in Iran - Mahdavi, Sayed Mosayeb; Kazemi, Shahrooz; Mohammad-Doustaresharaf, Mojtaba; Asadi, Mahdieh (Zootaxa, 2023)
A new species of the genus Pseudoleptus Bruyant, 1911 (Tenuipalpidae), Pseudoleptus avicennai sp. nov., is described and illustrated based on female specimens collected from bermudagrass, Cynodon dactylon (Poaceae), in Iran. This is the first report of C. dactylon as a host plant for Tenuipalpidae in Iran. In addition, the species Neopetrobia (Neopetrobia) mcgregori (Pritchard & Baker, 1955) (Tetranychidae) and Linotetranus sibiriensis Khaustov & Khaustov, 2023 (Linotetranidae) are recorded for the first time from Iran.